Think before you leap: cutaneous hypersensitivity to polytetrafluoroethylene arteriovenous graft masquerading as infection. Issue 9 (6th September 2019) - Iqbal, Rabia; Bhandare, Deepti; St Louis, Myron; Ruchi, Rupam
Abstract : Polytetrafluoroethylene (PTFE) graft is a synthetic graft commonly used in chronic haemodialysis patients. Expected complications of synthetic grafts include infection, thrombosis, oedema and pain. PTFE is a non-textile graft that is chemically inert, electronegative and hydrophobic. Due to their chemical properties, PTFE grafts have lower risks of these adversities. We present a patient with a rare case of cutaneous hypersensitivity to a PTFE graft.